Stimulation of Awig-Awig in Character Development and Human Resources Improvement in the Traditional Village of Penglipuran - Kurnia Uthami, I.G.A Agung Dewi; Supriyadinata Gorda, A.A.N. Eddy (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
This study aims to examine awig-awig stimulation in developing character and improving human resources in Traditional Village of Penglipuran. A case study was conducted in the village. To answer research questions, interviews were conducted with village policy makers who have a good understanding of awig-awig and villagers who understand awig-awig and live under the awig-awig shade. This study uses purposive sampling. The data analysis was carried out in four steps, namely data collection, data reduction, data presentation and conclusion drawing/ verification. Validity tests of the research are credibility test, transferability test, dependability test, and confirmability test. This research reveals that stimulation of awig-awig of the Traditional Village of Penglipuran is (1) able to shape the character of the entire community according to Hindu religious values; (2) able to foster the village tourism by developing human resources based on local wisdom without being eroded by globalization, and (3) binding customary rules to make the community of the Penglipuran village remain firm and obedient to awig-awig in conjunction with the concept of Tri Hita Karana.